BIOLOGICALLY ACTIVE SUBSTANCES OF SPIRIT PRODUCTION WASTE - A. S. Kayshev; N. S. Kaysheva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
A content of biologically active compounds (BAC) with signified pharmacological activity in distillers grains was proved. It is prospective for applications of these grains as a raw material resource of pharmaceuticals. A composition of BAC distillers grains received from wheat, corn, barley, millet at different spirit enterprises which use hydro fermentative grain processing. Considering polydispersity of distillers grains they were separated on solid and liquid phases preliminary. Physical and chemical characteristics of distillers grains' liquid base were identified. Elementary composition of distillers grains is signified by active accumulation of biogenic elements (phosphorus, potassium, magnesium, calcium, sodium, iron) and low content of heavy metals. The solid phase of distillers grains accumulates carbon, hydrogen and nitrogen in high concentration. The liquid phase of distillers grains contains: proteins and amino acids (20-46%), reducing sugars (5,6%-17,5%), galacturonides (0,8-1,4%), ascorbic acid (6,2-11,4 mg%). The solid base of distillers grains contains: galacturonides (3,4-5,3%), fatty oil (8,4-11,1%) with predomination of essential fatty acids, proteins and amino acids (2,1-2,5%), flavonoids (0,4-0,9%), tocopherols (3,4-7,7 mg%). A method of complex processing of distillers grains based on application of membrane filtering of liquid phase and liquid extraction by inorganic and organic solvents of solid phase, which allows almost full extraction of the sum of biologically active compounds (BAC) from liquid phase (Biobardin BM) and solid phase (Biobardin UL). Biobardin BM comprises the following elements: proteins and amino acids (41-69%), reducing sugars (3,5-15,6%), fatty oil (0,2-0,3%), flavonoids (0,2-0,7%), ascorbic acid (17-37 mg%). Biobardin UL includes: oligouronids (16,4-19,5%), proteins and amino acids (11-21%), fatty oil (3,2-4,9%) which includes essential acids; flavonoids (0,6-1,5%), tocopherols (6,6-10,2 mg%), carotinoids (0,13-0,21 mg%). Proteins of Biobardins are inhomogeneous by their molecular mass and solubility in water and salt solutions. Both Biobardins are characterized by the mineral composition identical to the composition of relative distillers grains phase. During the experiments on animals practical nontoxicity and hepatotoxicity absence of Biobardins were established. Using prednisole stomach ulcers of rats as a model a signified gastroprotective influence of Biobardin BM was established. It was shown in a reduction of the number of ulcerative and hemorrhagic blennoses, secretory and proteolytic functions of stomach. Models of electroreduction, peroxide oxidation of lipids (POL) of oleic acid, POL of egg yolk, and rats' hepatitis proved signified antioxidant activity of Biobardin UL which exceeds comparable substances by 8,3-30,1%; absence of fatty degeneration of rats' lever was shown under the influence of Biobardin UL. Composition of Biobardin BM and Biobardin UL pills as rational medicine form was justified and designed. Distillers grains processing allows reduction of industrial waste toxicity index - chemical consumption of oxygen (CCO) by 74%, making distillers grains ecologically-friendly waste water.